1969
DOI: 10.1037/h0026951
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the instructional sets to remember and to forget on short-term retention: Studies of rehearsal control and retrieval inhibition (repression).

Abstract: Five short-term memory experiments are reported which examined whether the instructional set to forget affects trace formation or trace retrieval. The experimental paradigms included a manipulation of covert rehearsal efforts, variation in the temporal point in the memory sequence at which a remember or forget instructional cue is introduced, a "latent memory" design in which 5s perceived identical stimuli under shifting instructional sets, and a procedure in which identical stimuli were repeatedly perceived u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 6 publications
0
51
0
Order By: Relevance
“…The present experiments were designed to replicate and extend the work of Weiner and Reed (1969). In particular, their finding of equivalent recall for Rand F items following repetition could be explained as enhanced encoding of the F items at repetition, thus compensating for the initial encoding deficit resulting from the F cues.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…The present experiments were designed to replicate and extend the work of Weiner and Reed (1969). In particular, their finding of equivalent recall for Rand F items following repetition could be explained as enhanced encoding of the F items at repetition, thus compensating for the initial encoding deficit resulting from the F cues.…”
mentioning
confidence: 75%
“…The work of Weiner and Reed (1969) suggests that, even when subjects are awake, intent to forget enhances forgetting more than nonrehearsal. Yet recent data from our laboratory have shown that subjects describe their forgetting strategies simply as nonrehearsal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is a long history of empirical evidence for deliberate forgetting of some kinds of memories (for reviews, see Bjork, 1998;Golding & Long, 1998;Golding & MacLeod, 1998;Johnson, 1994;MacLeod, 1998). Directed forgetting (DF), or intentional forgetting, has been found with a wide range of stimuli, including trigrams (Weiner, 1968;Weiner & Reed, 1969), digits (Brown, 1954), word pairs (Reitman, Malin, Bjork, & Higman, 1973), categorized words (MacLeod, 1975), pictures (Basden & Basden, 1996), sentences (Geiselman, 1974), and even navigation instructions (Golding & Keenan, 1985). However, whether it is reasonable to generalize from such stimuli to autobiographical events is debatable.…”
mentioning
confidence: 99%
“…For example, Weiner and Reed (1969) used a variant of this procedure to investigate repression by giving subjects a series of letter trigrams to learn with instructions either to remember and rehearse the trigrams, to remember but not rehearse them, or to forget them. They were given a secondary task of number shadowing during the retention interval after each trigram.…”
mentioning
confidence: 99%